Proceedings of the 6th IMEKO TC16 Conference on Pressure and Vacuum Measurement 2023
DOI: 10.21014/tc16-2022.117
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic Effects in a Gas Modulated Invar-Based Dual Fabry-Pérot Cavity Refractometer Addressing 100 Kpa of Nitrogen

Abstract: An Invar-based dual Fabry-Pérot cavity refractometer used for assessments of pressure by the gas modulation refractometry (GAMOR) methodology has been scrutinized with respect to the influence of thermodynamic effects (pV-work) that originates from the gas exchange process when 100 kPa of nitrogen is addressed. It is shown that the actual temperature variation of the cavity spacer solely is a fraction of the previously assessed upper limits (0.5 mK/100 kPa), limited to sub-parts-permillion (ppm) levels. This f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…It was found that, due to the small dimensions of the Invar-based FPC system and the thermal properties of Invar, for the case with 30 kPa of N2 being assessed, the temperature of the gas species is within 1 mK of the cavity wall in less than 1 s, that after 10 s an upper limit for the temperature increase at any point of the spacer is 1 mK, and that, at the end of the gas filling, the difference in temperature between the gas and the locations of the temperature probes in the spacer block are less than 0.3 mK [13]. A subsequent study has indicated that the actual fluctuations of the temperature are markedly less than the predicted upper limits, implying that the system has similar properties when 100 kPa of N2 is addressed [14]. This implies that assessments made by use of the GAMOR methodology are not significantly affected by any temperature fluctuations due to the filling and evacuation of gas.…”
Section: Wp1: Pressure Measurements Based Onmentioning
confidence: 92%
“…It was found that, due to the small dimensions of the Invar-based FPC system and the thermal properties of Invar, for the case with 30 kPa of N2 being assessed, the temperature of the gas species is within 1 mK of the cavity wall in less than 1 s, that after 10 s an upper limit for the temperature increase at any point of the spacer is 1 mK, and that, at the end of the gas filling, the difference in temperature between the gas and the locations of the temperature probes in the spacer block are less than 0.3 mK [13]. A subsequent study has indicated that the actual fluctuations of the temperature are markedly less than the predicted upper limits, implying that the system has similar properties when 100 kPa of N2 is addressed [14]. This implies that assessments made by use of the GAMOR methodology are not significantly affected by any temperature fluctuations due to the filling and evacuation of gas.…”
Section: Wp1: Pressure Measurements Based Onmentioning
confidence: 92%